2018
DOI: 10.1002/cpim.62
|View full text |Cite
|
Sign up to set email alerts
|

Efficient CRISPR/Cas9‐Mediated Mutagenesis in Primary Murine T Lymphocytes

Abstract: The ability to alter gene expression directly in T lymphocytes has provided a powerful tool for understanding T cell biology, signaling, and function. Manipulation of T cell clones and primary T cells has been accomplished primarily through overexpression or gene‐silencing studies using cDNAs or shRNAs, respectively, which are often delivered by retroviral or lentiviral transduction or direct transfection methods. The recent development of CRISPR/Cas9‐based mutagenesis has revolutionized genomic editing, allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…In particular, we focused on cCbl and PI3K, both of which show defective activation in Crk-deficient T cells. To target these proteins, we implemented a CRISPR KO system in primary mouse T cells (33). T cell blasts cultured from Cas9-expressing mice were transduced with retroviral vectors containing non-targeting (NT), cCbl, or PI3Kδ gRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, we focused on cCbl and PI3K, both of which show defective activation in Crk-deficient T cells. To target these proteins, we implemented a CRISPR KO system in primary mouse T cells (33). T cell blasts cultured from Cas9-expressing mice were transduced with retroviral vectors containing non-targeting (NT), cCbl, or PI3Kδ gRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The recently described gRNA retroviral transfer vector MRIG (33) was modified to express the puromycin resistance gene in place of GFP. Specific gRNAs were cloned into this vector exactly as described in (33). The gRNA sequences used in this study were as follows, NT: 5' GCGAGGTATTCGGCTCCGCG, cCbl: 5' TGTCCCTTCTAGCCGCCCAG, and PI3Kδ: 5' GGAGCGTGGGCGCATCACGG.…”
Section: Retroviral Productionmentioning
confidence: 99%
“…Researchers have created Cas9 transgenic mice ( 8 , 10 ). To manipulate their T cells, however, gRNAs are still introduced per retroviral transduction ( 7 , 8 ). Apart from the fact that this is more tedious and time consuming than electroporation, retroviral backbones could cause immunogenicity and toxicity ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…With this, they are even able to transduce non-activated T cells with high efficiency ( 3 ). Alternatively, pre-stimulated T cells from Cas9 transgenic mice can be mutated by guide (g) RNAs, the combination of crRNA and tracrRNA, which are delivered via retroviral transduction ( 7 , 8 ). Since studies have shown that at least sole mRNA can be successfully electroporated into T cells ( 9 ), we attempted to make use of Cas9 transgenic mice ( 10 ) and to develop efficient gRNA-only delivery into naive T cells using a nucleofection technique.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the sgRNA is introduced by γ-retroviral transduction into Cas9 transgenic mice expressing the Cas9 enzyme endogenously in T cells. γ-Retroviruses efficiently infect activated proliferating mouse T cells (Zhang et al , 2003 ; Kerkar et al , 2011 ), and this approach has been shown to effectively target mouse T cell genes (Huang et al , 2019 ; Roy et al , 2020 ). Retroviral delivery of sgRNAs has the important added benefit that retroviruses are integrated into the genome, and hence can be identified by next-generation sequencing allowing for pooled CRISPR/Cas9-mediated screening.…”
Section: Crispr/cas9-mediated Gene Ko In T Cellsmentioning
confidence: 99%